RECONSTRUCTION OF ARTICLE 34 OF THE LAW ON GENERAL PROVISIONS AND TAX PROCEDURES (KUP LAW) ON THE GOVERNANCE OF THE ACCOUNTABILITY OF THE DIRECTORATE GENERAL OF TAXES FOR THE MISUSE OF DIGITAL IDENTITY IN THE E-FAKTUR SYSTEM - Natalia Ratih Jatmikani; Ariy Khaerudin; Femmy Silaswaty (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Digital-based tax services require the Directorate General of Taxes to maximize the protection of personal data in the form of digital taxpayer identities, such as the Population Identification Number (KIP), which is currently used as the Taxpayer Identification Number. The purpose of this research is to analyze the reconstruction of Article 34 of the General Provisions of Taxation Law concerning the governance of the Directorate General of Taxes' accountability for the misuse of digital identities in the system.and-Invoices. The study was conducted using a normative method with a statutory and conceptual approach. The data used was secondary data collected through literature review and analyzed qualitatively and descriptively. The results indicate that there are no laws and regulations specifically governing the Directorate General of Taxes' accountability in the event of misuse of digital identities within the system.and-Invoices because so far the form of prohibition regulated is limited to the dissemination of personal data by officials without affecting electronic systems. Therefore, it is necessary to reconstruct Article 34 of the General Provisions of Taxation Law by adopting the provisions in Article 47 of the Personal Data Protection Law, which places the Directorate General of Taxes as the controller of personal data in both conventional and digital forms, thereby providing certainty and legal protection for taxpayers. Forms of accountability that can be added include administrative sanctions and criminal sanctions for any form of possible data leaks that are not caused by the error or negligence of tax officials.